Active transport of glucose across the jejunal epithelium decreases with age in broiler chickens. (9th February 2019) - Shibata, M; Takahashi, T; Kozakai, T; Kakudo, M; Kasuga, S; Azuma, Y; Kurose, Y
ABSTRACT: Intestinal glucose absorption varies with growth; however, the dynamics of these variations has not been yet fully elucidated in broiler chickens. The present study aimed to compare jejunal glucose uptake and maltose digestion in broilers of 2 different ages, i.e., 1- vs. 5 wk old. Oral D-maltose gavage, everted sac, and Ussing chamber experiments were carried out to investigate intestinal glucose absorption and mRNA expression of glucose-transport-related genes as well as jejunal maltase activity. Upon gavage, glucose concentrations peaked at 10 min post-administration in 1-wk-old chicks, while they peaked at 40 min in 5-wk-old chickens. Glucose concentrations at 10 min were significantly higher in the 1-wk-old chicks ( P = 0.010). Using the everted sacs experimental setup, 5 intestinal regions i.e., duodenum, proximal jejunum, distal jejunum, proximal ileum, and distal ileum, were targeted to examine D-maltose digestion and glucose transport across the intestinal mucosa. In the distal and proximal ileum, glucose concentrations were found to be significantly higher in the serosal compartment of the 1-wk-old chicks upon incubation with D-maltose (25 mM) ( P < 0.05), while in the mucosal compartment the levels were significantly higher in the 5-wk-old chickens ( P < 0.05). An Ussing chamber setup was employed to measure glucose-induced short-circuit current ( ΔI sc ) in the mucosal epithelium of the jejunum. In response to the addition of D-maltose (10 mM) into the mucosal compartment, ΔI sc was significantly higher in the 1-wk-old chicks ( P = 0.018). Furthermore, no variations in jejunal maltase activity were observed between the 2 age groups. While jejunal glucose absorption was lower in the 5-wk-old chickens, the mRNA expression levels of jejunal SGLT1, GLUT2, and Na+/K+-ATPase did not show any significant differences between the 2 age groups. Our results suggest that the active transport of glucose across the jejunal epithelium decreases upon growth in broiler chickens but is not accompanied by any variations in maltase activity or in the expression of glucose-absorption-related genes.